Effect of Strain Rates on Tensile Behavior of Kenaf Fiber and Rice Husk Silica Reinforced Polypropylene Composites - Abdul Latif, Noradila; Mohd Joharudin, Nurul Farahin (International Journal of Integrated Engineering, 2019)
The expanding interest for eco-accommodating materials, expanding exhaustion rate, and squeezing ecological controls have all set off a developing enthusiasm toward the field of composites. There is a demand for composites which not only possess good mechanical properties but also low cost, eco-friendly and lightweight. The objective of this study is to investigate the tensile behavior under elevated strain rates of kenaf fiber and rice husk silica reinforced polypropylene composites at different grades of rice husk silica (89.09% and 94.05%) content. The samples of composite materials were prepared by using injection molding at different composite percentage of kenaf fiber, rice husk silica and polypropylene composites. Tensile test was carried out to determine the tensile stresses of the composite at the best composition ratio of kenaf fiber and rice husk silica. Generally, the sample with 20 wt.% of kenaf fiber and 20 wt.% of rice husk silica which have high silica content exhibited the best yield stress, ultimate tensile strength and elongation which are 20.31MPa, 20.86MPa and 13.05% respectively. The result shows that 2nd grade with high silica content of rice husk silica has better behavior with increases the yield and ultimate tensile strength compared to results of 1st grade of rice husk silica.